Karakteristik tekan, bending dan morphology komposit mortar ringan diperkuat serat limbah tekstil - Sari, N.H.; Suteja, S.; Catur, A.D.; Jaya, D.P. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2023)
The composites was made from a foam mortar matrix with Hydrolized protein reinforced textile waste fiber and the compressive strength, flexural strength and fracture morphology characteristics of the composite have been reported. This study investigated the effectiveness of adding textile fiber waste to lightweight mortar composites to improve the mechanical characteristics of the composites, reduce weight and minimize production costs of mortar composites. Mortar composites are fabricated by varying the volume fraction of textile waste fiber from 0 to 1.2% (of the composite density). The results revealed that the addition of textile waste fiber to the mortar composites decreased bending strength and bending modulus. The maximum compressive strength of the mortar composite was obtained at a volume fraction of 0.6% textile fiber waste (0.30167 MPa) and the lowest compressive strength of 0.149 MPa was owned by the mortar composite without textile fiber waste (composite BTA). This phenomenon caused by the fiber pull out, interface bond between textile waste fiber and matrix, as shown from the SEM photo. The addition of excess textile fiber waste from optimal conditions reduces mechanical performance due to increased voids in the mortar composite. However, this strategy helpful to reduce the weight of the concrete, reduce production costs and reduce textile waste.